1991
DOI: 10.1113/jphysiol.1991.sp018865
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activation and c‐fos mRNA expression in rat neurosecretory neurones after systemic administration of cholecystokinin.

Abstract: SUMMARY1. The expression of c-fos mRNA in the rat hypothalamus was examined by in situ hybridization following systemic administration of cholecystokinin (CCK), a procedure known to activate magnocellular oxytocin neurones but not magnocellular vasopressin neurones.2. Conscious male rats were given a single i.P. injection of 50 jug/kg CCK. c-fos mRNA signal was apparent in the supraoptic and paraventricular nuclei in rats killed 10 min after injection but not in uninjected or saline-(vehicle) injected rats. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 35 publications
(43 reference statements)
1
29
1
2
Order By: Relevance
“…Northern analysis has confirmed that probe binding is specifically to mRNA corresponding in size to that reported for rat c-fos mRNA (Wisden et al, 1990). Hybridization in the hypothalamus is localized to neuronal cell bodies, and is blocked in the presence of an excess of cold oligonucleotide and by RNase A pretreatment of tissue sections (Hamamura et al, 1991;1992 perfused with fixative for standard immunocytochemistry using a polyclonal antibody raised against the N-terminal amino acids 2-17 of the Fos protein, as previously described (Luckman, 1992 (Figure 2a). Injection of MK-329 itself had no effect on the plasma oxytocin concentration at any dose used.…”
Section: Methodsmentioning
confidence: 68%
See 2 more Smart Citations
“…Northern analysis has confirmed that probe binding is specifically to mRNA corresponding in size to that reported for rat c-fos mRNA (Wisden et al, 1990). Hybridization in the hypothalamus is localized to neuronal cell bodies, and is blocked in the presence of an excess of cold oligonucleotide and by RNase A pretreatment of tissue sections (Hamamura et al, 1991;1992 perfused with fixative for standard immunocytochemistry using a polyclonal antibody raised against the N-terminal amino acids 2-17 of the Fos protein, as previously described (Luckman, 1992 (Figure 2a). Injection of MK-329 itself had no effect on the plasma oxytocin concentration at any dose used.…”
Section: Methodsmentioning
confidence: 68%
“…The profile of neuronal activation in the hypothalamus following systemic administration of CCK has been studied using products of the immediate-early gene c-fos as a marker. Within 10 min of CCK injection, c-fos mRNA is expressed in neurones of the supraoptic and paraventricular nuclei (Hamamura et al, 1991). In the supraoptic nucleus, Fos-like immunoreactivity (Fos-LI) is found exclusively in magnocellular oxytocin neurones following CCK injection, while in the paraventricular nucleus at least three neuronal populations express Fos-LI: the CRF neurones, and both magnocellular and parvocellular oxytocin neurones (Verbalis et al, 1991b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These vagal messages initiated by the intraperitoneal or intravenous administration of CCK activate several neuronal complexes in the brain, including the nucleus tractus solitarius, the lateral parabrachial nucleus, and the central nucleus of the amygdala, as assessed by expression of the early gene product c-fos (Hamamura et al 1991). The production of early satiety by CCK does not require an intact medial hypothalamus because it occurs in human subjects with hypothalamic injury and obesity (Boosalis et al 1992).…”
mentioning
confidence: 99%
“…Além disso, a vagotomia bloqueia a redução de ingestão provocada por injeção periférica de CCK, sugerindo que mensagens aferentes são geradas a nível hepático e gastroduodenal e encaminhadas ao cérebro via nervo vago. Essas mensagens ativam vários complexos neuronais cerebrais, incluindo o núcleo do trato solitário, o núcleo parabraquial lateral e o núcleo central da amíg-dala (85). É interessante que a produção de saciedade precoce pela CCK independe da integridade do hipotálamo medial, uma vez que ocorre em humanos com lesão hipotalâmica e obesidade.…”
Section: Peptídeos Agentes De Ação Periféricaunclassified